ESG Performance and Investment Efficiency in Sharia-Compliant Firms: Evidence from the JII-70 - Kufepaksi, Mahatma; Hendrawaty, Ernie; Warganegara, Doni Sagitarian; Rikanda Saputra, Adli (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Abstract: This study examines whether Shariah-compliant ESG performance enhances investment efficiency among firms included in the Jakarta Islamic Index 70 (JII-70) and how board characteristics condition this relationship. Using an unbalanced panel of 25 firms consistently listed in JII-70 from 2020–2023 (100 firm-years), investment inefficiency is measured as the residual from an expected-investment model, where lower residuals indicate higher efficiency. Fixed-effects panel regressions with White cross-section robust errors are employed after Chow, Hausman, and diagnostic tests. The results show that ESG scores are negatively and significantly associated with investment inefficiency in most specifications, implying that stronger ESG performance improves capital allocation. Board gender diversity reduces inefficiency on average but weakens the marginal efficiency gains of ESG. Board independence does not significantly moderate the ESG–efficiency link. By contrast, board nationality diversity reinforces the positive effect of ESG on efficiency, while larger boards tend to increase the baseline level of inefficiency. Overall, the findings indicate that governance configuration plays a critical role in translating Shariah-aligned ESG initiatives into more efficient investment decisions among JII-70 constituents. Keywords: Board characteristics, ESG, investment efficiency, Jakarta Islamic Index 70